2019
DOI: 10.3389/fphar.2019.00948
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines Safety in Children and in General Population: A Pharmacovigilance Study on Adverse Events Following Anti-Infective Vaccination in Italy

Abstract: Background: The concern for adverse events following immunization (AEFI) and anti-vaccination movements that lacked scientific evidence-based supports may reduce vaccine uptake in the general population. Thus, the aims of the present study were to characterize AEFI in general population (all age groups), in terms of frequency, preventability, and seriousness and to define predictors of their seriousness in children. Methods: A retrospective study was performed on suspected AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…This is an observational retrospective study performed on data retrieved by pharmacovigilance reports of suspected ADE collected between January 1, 2007 and December 31, 2018 in the EDs participating to the MEREAFaPS Study ("Monitoraggio Epidemiologico delle Reazioni e degli Eventi Avversi da Farmaci in Pronto Soccorso" -"Epidemiological Monitoring of Adverse Drug Reactions and Events leading to Emergency Department"), an ongoing multicentre study of active pharmacovigilance (Lombardi et al, 2018;Lombardi et al, 2019). This is the first nationwide pharmacovigilance study performed in Italy with an "active" approach and based on electronic ED medical records containing detailed information on patient populations, thereby allowing consideration of modifying factors such as polypharmacy and comorbidity, as well as sociodemographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an observational retrospective study performed on data retrieved by pharmacovigilance reports of suspected ADE collected between January 1, 2007 and December 31, 2018 in the EDs participating to the MEREAFaPS Study ("Monitoraggio Epidemiologico delle Reazioni e degli Eventi Avversi da Farmaci in Pronto Soccorso" -"Epidemiological Monitoring of Adverse Drug Reactions and Events leading to Emergency Department"), an ongoing multicentre study of active pharmacovigilance (Lombardi et al, 2018;Lombardi et al, 2019). This is the first nationwide pharmacovigilance study performed in Italy with an "active" approach and based on electronic ED medical records containing detailed information on patient populations, thereby allowing consideration of modifying factors such as polypharmacy and comorbidity, as well as sociodemographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been published on ADEs as a cause of ED admissions, but none of those available in the literature has been conducted at national level and for a long observational period (Perrone et al, 2014;Lombardi et al, 2018;Lombardi et al, 2019). Furthermore, few studies evaluated the presence of specific variables among population and/or medication characteristics which can contribute to an ADE as a cause of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…age, sex etc.) and clinical status; (ii) AE, codified using the Medical Dictionary for Regulatory Activities (MedDRA) classification, and described using the preferred terms (PT) and system organ class (SOC) most frequently reported; (iii) AE degree of seriousness, classified according to the World Health Organisation criteria as fatal, life‐threatening, or requiring hospitalisation of the patient, or causing serious/permanent disability, or causing congenital abnormalities, or other clinically relevant conditions (https://apps.who.int/iris/bitstream/handle/10665/67378/WHO_EDM_QSM_2002.2.pdf;jsessionid=EF4F54EFF6FBD634E21D2C075ADCA3C0?sequence=1; 29661234); (iv) AE outcome; (v) ongoing cannabis therapy (i.e. product type, indication, dosage, length of exposure, and administration route); (vi) concomitant medications.…”
Section: Methodsmentioning
confidence: 99%
“…An active monitoring system of ADR showed that neonates (< 1 years) have an higher risk of ADR appearance than children (7-14 years) (Menniti-lppolito et al, 2000). Antibacterial for systemic use were reported as the drugs with the highest frequency of ADRs (Carnovale et al, 2014;Ferrajolo et al, 2014;Lombardi et al, 2018) In the recent years, the number of vaccine-hesitant patients as well as the movements against vaccination grew up (Lombardi et al, 2019). Consequently, immunization coverage of children sharply decreased (Signorelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%